(untitled) (Revista Lusófona de Educação, 2026)
Department of Didactics and School Organization, and is widely recognized as a leading reference in the field of Educational Sciences. His academic and scientific trajectory stands out particularly in the areas of inclusive education, interculturality, attention to diversity, and teacher education, playing a significant role in the development of pedagogical approaches grounded in equity and social justice.Throughout his career, he has devoted himself to the critical analysis of contemporary educational challenges, especially in school contexts marked by increasing cultural, social, and linguistic plurality. His research has contributed to deepening the debate on inclusion policies and practices, the integration processes of migrant and minority students, as well as strategies for pedagogical innovation aimed at educational transformation. In this regard, his work highlights the need to rethink traditional educational models, promoting more participatory, democratic, and inclusive school environments that are responsive to the diverse realities and needs of students. With a well-established and widely recognized body of scientific work, Juan José Leiva Olivencia has made significant contributions to the study of intercultural coexistence, the construction of inclusive educational communities, and the role of schools as privileged spaces for citizenship. His work extends beyond academia, also involving community-based intervention projects and educational initiatives that strengthen the connection between research, pedagogical practice, and social commitment. This professional path has reinforced the idea of schools as spaces of encounter, dialogue, and intercultural coexistence, capable of addressing inequalities and promoting the effective inclusion of all students. This interview with Professor Juan José Leiva Olivencia focuses on current challenges in inclusive and intercultural education, within a context marked by increasing diversity in schools and the urgent need for fairer and more effective educational responses. Drawing on his scientific experience and main research lines, the interview addresses issues related to educational inclusion, school coexistence, teacher training, public policies, and pedagogical innovation oriented toward equity. The main objective of this interview is to deepen a critical, well-grounded, and up-to-date reflection on the role of education in promoting social justice, respect for diversity, and the development of more democratic and participatory educational communities. It thus seeks to contribute to academic debate and to the improvement of educational practices in different contexts, reinforcing the commitment to a more inclusive, human-centered, and socially responsible school.